Effect of Teprenone on Gastric Mucosal Injury Induced by Helicobacter pylori in Rats - Saita, Hiroshi; Murakami, Motonobu (Arzneimittelforschung, 2000)
The aim of this study was to investigate the protective effect of gastric mucus against Helicobacter pylori-induced gastric mucosal injury, measuring intramucosal mucus and the surface hydro-phobicity. Male Sprague-Dawley rats’ stomachs were exposed to H. pylori suspension (1 × 105 ml) plus 1 ml of urea solution (400 mg/dl) with gastric ischemia (withdrawal of 3 ml of blood) for 60 min, 60 min after pretreatment with teprenone (CAS 6809-52-5) (50 mg/rat, intragastric). The control rats were treated in the same manner without pretreatment with teprenone. A high concentration of intragastric ammonia was generated 60 min after administration of H. pylori plus urea in both the control and the teprenone-pretreated rats. A reduction in transmucosal potential difference, formation of hemorrhagic gastric lesions, and impairment in both intramucosal mucus and surface hydrophobicity were observed in the corpus of the control rats. However, the pretreatment with teprenone prevented such a reduction in potential difference and the development of gastric lesions against ammonia through the preservation of gastric mucus. The preservation of gastric mucus might protect gastric mucosa against attacks by H. pylori, suggesting that the mechanism of H. pylori-associated gastric injury is associated with the decrease in gastric mucus.
Keywords: Ammonia; CAS 6809-52-5; Gastric mucus; Helicobacter pylori; Teprenone, effect on gastric mucosal injury, rat